Pengembangan Media Pembelajaran Permainan Kartu Yugioh! Pada Mata Pelajaran Korespondensi di SMK Krian 2 Sidoarjo - Riskia Nur Firdaus; Durinda Puspasari (Jurnal Pendidikan Administrasi Perkantoran (JPAP), 2020)
Correspondence Subjects are one of the productive subjects that must be taken by SMK students (Vocational High Schools), especially vocational students in the field of expertise in OTKP (Office Management Automation) found in class X OTKP. This subject covers Basic Competencies in Applying Communication by Telephone in Indonesian. The implementation of learning conducted by the teacher to explain the material  using power point learning media, but the teacher has never makes variations of learning on the power point media and the teacher explains still using the lecture method. This causes students to tend to feel bored in learning that is too monotonous. In addition, results of  distribution of questionnaires to use of power point learning media used by teachers, namely 25% of students tend to feel bored in using power point media, 15% of students are not interested in power point media used by teachers, 15% of power point media used by the teacher is not easily understood by students, and 45% of students can understand the delivery of material using power point media from the teacher. This research was conducted with the aim to find out the results of developing Yugioh card game learning media! on the subject of correspondence at SMK Krian 2 Sidoarjo. So with the Yugioh! card game learning media can help the learning process is more interesting and make students motivated to better understand learning material. During the learning process students can play an active role, cooperate with each other, and can think critically. The type of research used is Research and Development (R&D) with the 4D development model is namely define, design, develop, and disseminate. However, this research was only carried out at the design stage only due to limitations in this study. Based on the results of the study, at the stage of define carried out an analysis of the things needed in media develop, namely the early analysis, student analysis, task analysis, concept analysis, and specification of learning objectives. After defining, the design phase is carried out which is carried out several stages, namely the design of the material into learning media, the initial design of instructional media, determining the contents of the card and the design of the card, after the next design is carried out media printing. So it can be concluded the development of Yugioh! card game learning media can help the learning process more interesting and make students better understand the learning material.